The level of cytokines IL-4, IL-12p40, IFN-y during acute toxoplasmosis - Abdullah, Dina A.; mahmood, Maha A.; AL hatemi, Mohammed D. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: the different roles of cytokines IL-4, IL-10, IL-12p40, IFN- during acute toxoplasmosis disease in pregnant women.